Audiovisual feedback device use by health care professionals during CPR: A systematic review and meta-analysis of randomised and non-randomised trials - Kirkbright, S.; Finn, Judith; Tohira, Hideo; Bremner, A.; Jacobs, Ian; Celenza, A. (Elsevier, 2014)
Objectives: A systematic appraisal of the literature to determine if audiovisual feedback devices can improve CPR quality delivered by health care practitioners (HCPs) and/or survival outcomes following cardiac arrest. Methods: We searched the Cochrane Central Register of Controlled Studies (CENTRAL) on The Cochrane Library, MEDLINE, EMBASE, CIHAHL and AUSTHEALTH in May 2013 for experimental and observational (human or manikin) studies examining the effect of the use of audiovisual feedback devices by HCPs in simulated and actual cardiac arrest. The primary outcome for human studies was survival to hospital discharge with good neurologic outcome. Secondary outcomes were other survival data and quality of CPR performance; the latter was also reported for manikin studies. Results: Three human interventional studies (n = 2100) and 17 manikin studies met the inclusion criteria. Overall quality of included studies was poor, with significant clinical heterogeneity. All three human studies reported no significant change to any survival outcomes despite improvement in chest compression(CC) depth by 2.5 mm (95% CI 0.9–4.3), CC rate 6 min-1 closer to 100 (95% CI 2.4–10.7) and a reduction in no-flow fraction by 1.9% on meta-analysis. Manikin studies showed similar improvement sin CC parameters. Conclusion: In both manikin and human studies, feedback during resuscitation can result in rescuers providing CC parameters closer to recommendations. There is no evidence that this translates into improved patient outcomes. The reason for this is not yet evident and further patient centered research is warranted.